2023
DOI: 10.59670/ml.v21is1.5939
|View full text |Cite
|
Sign up to set email alerts
|

The Integration and Utilization of Artificial Intelligence (AI) in Supporting Older/Senior Lecturers to Adapt to the Changing Landscape in Translation Pedagogy

Nisar Ahmad Koka

Abstract: The incorporation of Artificial Intelligence (AI) in translation pedagogy has continued to change the intricacies of the field in such a way that translation educators are expected to frequently update themselves with current Artificial Intelligence (AI) translation tools. In the context of this dynamic pedagogical landscape, translation educators; especially, older/senior lecturers might find it difficult in adjusting to the changing requirements of instructional methods and educational processes. In the ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Furthermore, concerns about a decline in the quality of work due to digitalization in the near future are unfounded in the field of translation. In addition, Koka (2024) examined the perspectives of chosen translation educators to gather their insights on leveraging AI to assist senior lecturers in adapting to the evolving landscape of translation pedagogy. The research revealed that senior lecturers perceived the integration of AI tools in translation pedagogy as beneficial, facilitating more effective teaching and learning experiences in the field of translation.…”
Section: Translators' Attitudes Towards Ai-based Translationmentioning
confidence: 99%
“…Furthermore, concerns about a decline in the quality of work due to digitalization in the near future are unfounded in the field of translation. In addition, Koka (2024) examined the perspectives of chosen translation educators to gather their insights on leveraging AI to assist senior lecturers in adapting to the evolving landscape of translation pedagogy. The research revealed that senior lecturers perceived the integration of AI tools in translation pedagogy as beneficial, facilitating more effective teaching and learning experiences in the field of translation.…”
Section: Translators' Attitudes Towards Ai-based Translationmentioning
confidence: 99%
“…The multimedia teaching and evaluation system, as a component of instructional media, is not only a good content channel but is also instantly accessible from anywhere (Lin, 2021). It aids in creating a productive conversation area for students, professors, and other students because it has opened up numerous communication channels (Koka, 2024). Chen believes that instructional assessment, as an important part of the modern education system, is not only to assess the teaching results but also to make dynamic assessments of the whole stage of education (Novawan et al, 2024).…”
Section: Literature Reviewmentioning
confidence: 99%